Види роду Tilia L. у Національному дендропарку “Софіївка” НАН України - Vegera, L.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The results of Tіlia L. species and forms inventorying in the National Dendrological Park Sofiyivka of the NAS of Ukraine are given. The taxonomic composition increase dynamics of the genus in the Dendrological Park plantations is demonstrated over the period of 1796–2010.